New approaches in W gravities - Abreu, EMC; Dutra, Alvaro de Souza [UNESP]; Wotzasek, C. (American Physical Soc, 2002)
We devote effort to studying some nonlinear actions, characteristic of W theories, in the framework of the soldering formalism. We disclose interesting new results concerning the embedding of the original chiral W particles in different metrical spaces in the final soldered action; i.e., the metric is modified by the soldering interference process. The results are presented in a weak field approximation for the W-N case when Ngreater than or equal to3 and also in an exact way for W-2. We promote a generalization of the interference phenomenon to W-N theories of different chiralities and show that the geometrical features introduced can yield a new understanding of the interference formalism in quantum field theories.